2018
DOI: 10.1002/mus.26340
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and body mass index in Duchenne muscular dystrophy: Role of dietary intake

Abstract: Age dependent changes in BD in boys with DMD may be due to endogenous metabolic factors related to the underlying disease process and to disease-related mobility impairments. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…Due to weight gain, short stature, loss of muscle mass, and fat mass accumulation, body mass index (BMI) is not the best way to assess the nutritional status in DMD patients [8,9]. DMD boys had lower levels of body cell mass and hydration compared with the healthy population described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to weight gain, short stature, loss of muscle mass, and fat mass accumulation, body mass index (BMI) is not the best way to assess the nutritional status in DMD patients [8,9]. DMD boys had lower levels of body cell mass and hydration compared with the healthy population described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the %FM, a significant prevalence of high adiposity was found in all groups with increased fat mass with age. Likewise, Bernabe-García et al (Bernabe-García et al, 2019) found that as age advances, the fat mass increases while lean mass decreases. Besides, Caromano et al (Caromano et al, 2010) noticed that body fat accumulation is also influenced by a sedentary lifestyle and may not reflect weight change due to loss of lean mass.…”
Section: Discussionmentioning
confidence: 94%
“…In clinical practice, weight gain in DMD is often seen during the transition to the nonambulatory stage, suggesting decrease in physical activity may play an important role, with accompanying changes in body composition. Multiple studies confirm that patients in their non-ambulatory stage have a higher BMI-z score in general [5,11]. Other factors which can cause weight gain are corticosteroid use and caloric intake [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…al. [11] in a corticosteroid naive DMD population, for which they compared caloric intake with the recommended caloric intake. They found high caloric intake at preschool age compared to the recommended caloric intake and found no associations between caloric intake and prediction of body fat mass and lean mass.…”
Section: Introductionmentioning
confidence: 99%